2010
DOI: 10.17221/123/2009-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of growing conditions on starch and protein content in triticale grain and amylose content in starch

Abstract: The effect of growing conditions on starch and protein content in triticale grain and amylose content in starch was studied on winter triticale cvs. Kitaro, lupus, lamberto and ticino harvested in 2006 and 2007 in Humpolec and Pernolec, Czech republic. Dry matter of the investigated triticale grain contained 62.4-70.9% of starch. The starch content and amylose content in starch were significantly affected by cultivar and year. Statistical analysis did not confirm that starch content and amylose content in star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
31
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 10 publications
(6 reference statements)
16
31
1
Order By: Relevance
“…Starch content differed across the locations since quality of grain depend on interplay between the genetic characteristics of the plant and external factors that influence plant growth such as climate, soil and management practices. In this study, the different starch content among sites contradicted the findings by Buresova et al (2010) who indicated that starch content was significantly affected by cultivar and year. They indicated that starch content was not significantly influenced by growing variant or site.…”
Section: Maize Seed Starchcontrasting
confidence: 99%
See 1 more Smart Citation
“…Starch content differed across the locations since quality of grain depend on interplay between the genetic characteristics of the plant and external factors that influence plant growth such as climate, soil and management practices. In this study, the different starch content among sites contradicted the findings by Buresova et al (2010) who indicated that starch content was significantly affected by cultivar and year. They indicated that starch content was not significantly influenced by growing variant or site.…”
Section: Maize Seed Starchcontrasting
confidence: 99%
“…They indicated that starch content was not significantly influenced by growing variant or site. The starch content of maize grains in this study differed across the seasons and this corroborates the findings the findings by Buresova et al (2010) who reported that starch content was significantly affected by weather during growing season. They indicated that warm weather during the growing season had a significant positive effect on starch content.…”
Section: Maize Seed Starchsupporting
confidence: 92%
“…In general, triticales contain around 62.4-70.9% of starch with approximately 20.8-26.4% of amylose content (Burešová, Sedláčková, Faměra, & Lipavský, 2010). According to previous reports, substituted triticales contain lower amounts of amylose than complete triticales (Navarro-Contreras et al, 2014), which have been related to the size of starch granules (Ao & Jane, 2007).…”
Section: Introductionmentioning
confidence: 96%
“…16 Triticale grain dry matter contains 62.4%-70.9% starch, a content that is dependent upon cultivar and year. 17 A recent scanning electron microscopy study of triticale starch granules during endosperm and seed development indicated unique and inherent structures, such as channels or pores that may facilitate the flow of hydrolytic enzymes into the granule matrix. 18 In addition, triticale starch has the apparent advantages of low phenolic acids content that otherwise negatively impacts starch hydrolysis, and a lower gelatinization temperature (of 65-68°C) compared to those of barley, wheat, and corn (in the range of 72-75°C; personal communication, T. Vasanthan, University of Alberta).…”
Section: Introductionmentioning
confidence: 99%